DETERMINATION OF EFFICIENCY OF DEFOLIATION IN MEDIUM-FIBER COTTON VARIETIES - M.M.Ubaydullayev; Ne’matova F.J; Marufjonov A (Galaxy International Interdisciplinary Research Journal, 2021)
The foreign Ento-Dephol showed a higt result, when guza couses open 30-40% while using 0.200 litres of defoliation for each hectar in order to defoliante cotton artificially.7.0 litres use of defoliation gave better result regarding to the other alternatives.